The SUI GENERIS SEKOLAH BERBASIS PESANTREN : STUDI KOMPARASI SMP AN-NIDA DAN MTS TAKHASSUS AL-QUR’AN WONOSOBO - Lailiyah, Siti; Elsyam, Robingun Suyud; Nihayah, Rohatun (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
This article aims to examine the Sui Generis of Islamic Boarding School-Based Schools: A Comparative Study of An-Nida Middle School and Takhassus Al-Qur'an MTs Wonosobo, by focusing on the characteristics of the institution, which previous researchers did not emphasize. This article is field research with a qualitative approach that focuses on intentionality through in-depth interviews. The research findings show that Islamic boarding school-based schools have distinctive characteristics (Sui Generis) that differentiate them from other educational institutions. Each of these institutions has characteristics that make them continue to exist and have different consumers. This diversity makes masterpieces created by central figures from each of these institutions. The meeting point of this diversity, namely that they all have the same goal, in the context of tafaqquh fi al-din (deepening religious knowledge). Through in-depth interviews it was found that Sui Generis at An-Nida' Islamic Boarding School Middle School, was based on the Kulliyatul Mu’allimin Al-Islamiyah (KMI) method, while at MTs Takhassus Al-Qur'an, it emphasized mastery of the yellow book. Research implications: the importance of understanding differences from Islamic boarding school-based schools as Sui Generis, not as a division. The research recommends that experts and researchers research further into more specific areas and deeper essence.